Spoon River America : Edgar Lee Masters and the myth of the American small town - Stacy, Jason, 1970- (University of Illinois Press, 2021)
"A literary and cultural milestone, Spoon River Anthology captured an idea of the rural Midwest that became a bedrock myth of life in small-town America. Jason Stacy places the book within the atmosphere of its time and follows its progress as the poetry took root and thrived. Published by Edgar Lee Masters in 1915, Spoon River Anthology won praise from modernists while becoming an ongoing touchstone for American popular culture. Stacy charts the ways readers embraced, debated, and reshaped Masters's work in literary controversies and culture war skirmishes; in films and other media that over time saw the small town as idyllic then conflicted then surreal; and as the source of three archetypes-populist, elite, and exile-that endure across the landscape of American culture in the twenty-first century. A wide-ranging reconsideration of a literary landmark, Spoon River America tells the story of how a Midwesterner's poetry helped change a nation's conception of itself"--